Targets of Neutrophil Influx and Weaponry: Therapeutic Opportunities for Chronic Obstructive Airway Disease. (15th May 2017) - Mårdh, Carina Kärrman; Root, James; Uddin, Mohib; Stenvall, Kristina; Malmgren, Anna; Karabelas, Kostas; Thomas, Matthew
Abstract : Neutrophils are important effector cells of antimicrobial immunity in an acute inflammatory response, with a primary role in the clearance of extracellular pathogens. However, in respiratory diseases such as asthma and chronic obstructive pulmonary disease (COPD), there is excessive infiltration and activation of neutrophils, subsequent production of reactive oxygen species, and release of serine proteases, matrix metalloproteinases, and myeloperoxidase—resulting in collateral damage as the cells infiltrate into the tissue. Increased neutrophil survival through dysregulated apoptosis facilitates continued release of neutrophil-derived mediators to perpetuate airway inflammation and tissue injury. Several target mechanisms have been investigated to address pathologic neutrophil biology and thereby provide a novel therapy for respiratory disease. These include neutrophil influx through inhibition of chemokine receptors CXCR2, CXCR1, and PI3K γ signaling and neutrophil weaponry by protease inhibitors, targeting matrix metalloproteinases and neutrophil serine proteases. In addition, neutrophil function can be modulated using selective PI3K δ inhibitors. This review highlights the latest advances in targeting neutrophils and their function, discusses the opportunities and risks of neutrophil inhibition, and explores how we might better develop future strategies to regulate neutrophil influx and function for respiratory diseases in dire need of novel effective therapies.